Co3Fe7/nitrogen-doped graphene nanoribbons as bi-functional electrocatalyst for oxygen reduction and oxygen evolution. (6th August 2018) - Joy, Jaison; Rajappa, Sivamathini; Pillai, Vijayamohanan K; Alwarappan, Subbiah
Abstract: In this work, we report a one-pot solvothermal strategy to synthesize Co3 Fe7 incorporated graphene nanoribbons (Co3 Fe7 ). An improved bi-functional electrocatalytic activity over the traditional electrocatalysts is exhibited by the Co3 Fe7 /nitrogen-doped graphene nanoribbon (NGNR) composite. For instance, this composite Co3 Fe7 /NGNRs depicted a lower overpotential of 350 mV than NGNRs (380 mV) and IrO2 (450 mV) to sustain 10 mA cm −2 for an oxygen evolution reaction in 1.0 M KOH. Furthermore, during an oxygen reduction reaction, the catalyst exhibited a four-electron pathway and it is interesting to note that its electrocatalytic behavior is on a par with commercial Pt/C. The enhancement in the electrochemical performance can be attributed to the synergistic effect that stems from the electrocatalytically active nitrogen atoms and metal alloy nanoparticles distributed uniformly over the graphene matrix. This unique composition of electrocatalyst is extremely beneficial for practical applications in fuel cells and metal–air batteries due to its high stability and sustained electrochemical activity.